The Linguistic Artistic Enhancements in the Holy Quran(Focusing on the First Ten Parts)Ghasem Bostani - Mortada Mohsen Jassim Al-Alaywi, Rese.; Seyyed Yusuf Mahfovi Mousawi, Dr.; Ghasem Bostani, Dr. (lark, 2024)
The science of "Badi'" (rhetoric and eloquence) is one of the three rhetorical sciences and one of the artistic rhetorical techniques. It was widely and innovatively used in the Quranic discourse to solidify meaning, enhance linguistic beauty, and manifest the divine eloquence. It is a science that encompasses the various ways of improving speech while adhering to the requirements of the context and the clarity of expression. It is divided into two categories: linguistic enhancements and semantic enhancements. Both categories of these enhancements have been extensively employed in the Quran and hold great importance. However, what are the most significant linguistic artistic enhancements used in the Quran? What are their examples? And what is their impact on divine discourse? Based on the descriptive-analytical method, relying on bibliographic research, the researcher will attempt to answer these questions by extracting the most important linguistic enhancements from the Quran, with a focus on the first ten parts. A brief explanation of each enhancement and its impact on the Quranic discourse will be provided. The research concluded that among the most important linguistic enhancements employed by the Quran are: rhyme, analogy, embroidery, assurance, harmony, dissection, good beginnings, repetition, clarification, and refuting objections. These enhancements contributed to the beauty of divine speech, solidifying the intended divine message, and demonstrating its miraculous nature in comparison to the speech of others